Opportunities and challenges in secondary stroke prevention: a mixed methods study. Issue 26 (18th December 2019) - White, Carole L.; Cantu, Adelita; Motz, Deb; Patterson, Michele; Caron, Jean-Louis; Birnbaum, Lee A.
Abstract: Purpose: To describe control of risk factors after stroke from the perspectives of the stroke survivor, the family, and healthcare professionals. Materials and methods: A mixed methods design was used, undertaken in two phases: i) qualitative study using focus group methodology to explore secondary stroke prevention and ii) survey of stroke survivors about use of technology and self-management of blood pressure (BP). Results: From the eight focus groups ( n = 33), three themes were identified: i) stroke is a wake-up call to do the right things; ii) challenges to doing the right things; and iii) role of technology in helping you to do the right things. Among survey respondents ( n = 82), most participants reported mobile phone ownership (93%), mostly smartphones (66%), and >80% identified a greater role for technology in supporting management of risk factors. Participants who reported monitoring BP at home were significantly more likely to know their target BP than those not monitoring at home (83 vs. 42%; p < 0.001) and more adherent with medications (78 vs. 52%; p = 0.016). Conclusions: These findings highlight the ongoing challenges with achieving risk factor control after stroke and the potential to utilise health information technology to engage stroke survivors in self-management of their risk factors. Implications for rehabilitation: Clinicians should be knowledgeable of the challenges that stroke survivors face in managing their risk factors after stroke and the role that they can play in providing tailored education. BP continues to be poorly controlled after stroke and there is opportunity for improvement. Stroke survivors and their families are receptive to using health information technology to support their risk factor control. Rehabilitation clinicians have an opportunity to incorporate different aspects of health information technology into their practice to support self-management of risk factors.